1987
DOI: 10.1002/1097-0142(19870201)59:3<540::aid-cncr2820590330>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of head and neck in patients with well-differentiated lymphocytic lymphoma

Abstract: Seventy-six cases of well-differentiated lymphocytic lymphoma (WDLL) were reviewed for evidence of additional malignancies. Of these, 18 patients (24%) had one to three further tumors; one half (nine) had squamous cell carcinoma (SCC). The head and neck area was the primary site in all but one case of SCC. The carcinomas were frequently multiple, recurrent, and clinically aggressive. The tumors showed unusually poor differentiation histologically. Actinic keratosis and basal cell carcinomas were frequently ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 12 publications
2
56
0
1
Order By: Relevance
“…Cancers of the breast and skin are among those reported to metastasise to nodes involved by lymphoma. [6][7][8] Cutaneous tumours associated with lymphoproliferative disorders have been documented in the literature. 4 9 Recently, Merkel cell carcinoma has been described in patients with CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Cancers of the breast and skin are among those reported to metastasise to nodes involved by lymphoma. [6][7][8] Cutaneous tumours associated with lymphoproliferative disorders have been documented in the literature. 4 9 Recently, Merkel cell carcinoma has been described in patients with CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, host immunosuppression can greatly increase the likelihood of SCC development, recurrence, and malignant spread [69–72]. Suppression may be due to an underlying malignancy, the active use of immunosuppresive agents during transplant therapy, or infection with HIV.…”
Section: Additional Prognostic Factorsmentioning
confidence: 99%
“…[630] Our study showed that the most common carcinoma arising with SLL/CLL was squamous cell carcinoma, which has also been reported in the past. [171920] The occurrence of these secondary tumors in SLL/CLL patients may be due to the good prognosis associated with an indolent lymphoma leading to long survival and sporadic occurrence of other tumors, particularly in older patients. Other possible etiologies include genetic predispositions, environmental factors and the potentially immunosuppressive role of the lymphoma itself or the treatment modalities used.…”
Section: Discussionmentioning
confidence: 99%